The mammalian neocortex new pyramidal neuron: a new conception - Marín-Padilla, Miguel (Frontiers in Neuroanatomy, 2014)
The new cerebral cortex (neocortex) and the new type of pyramidal neuron are mammalian innovations that have evolved for operating their increasing motor capabilities while essentially using analogous anatomical and neural makeups. The human neocortex starts to develop in 6-week-old embryos with the establishment of a primordial cortical organization, which resembles the primitive cortices of amphibian and reptiles. From the 8th to the 15th week of age, new pyramidal neurons, of ependymal origin, are progressively incorporated within this primordial cortex forming a cellular plate that divides its components into those above it (neocortex first layer) and those below it (neocortex subplate zone). From the 16th week of age to birth and postnatally, the new pyramidal neurons continue to elongate functionally their apical dendrite by adding synaptic membrane to incorporate the needed sensory information for operating its developing motor activities. The new pyramidal neuron’ distinguishing feature is the capacity of elongating anatomically and functionally its apical dendrite (its main receptive surface) without losing its original attachment to first layer or the location of its soma and, hence, retaining its essential nature. The number of pyramidal cell functional strata established in the motor cortex increases and reflects each mammalian species motor capabilities: the hedgehog needs two pyramidal cell functional strata to carry out all its motor activities, the mouse 3, cat 4, primates 5 and humans 6. The presence of six pyramidal cell functional strata distinguish the human motor cortex from that of others primates. Homo sapiens represent a new evolutionary stage that have transformed his primate brain for operating his unique motor capabilities, such as speaking, writing, painting, sculpturing and thinking as a premotor activity. Words used in language are the motor expression of thoughts and represent sounds produced by maneuvering the column of expiratory air by coordinated motor quivering as it passes through the larynx, pharynx, mouth, tongue, and lips. Homo sapiens cerebrum has developed new motor centers to communicate mental thoughts (and/or intention) through motor actions.